Métodos para superação de dormência em sementes de tabaco - Gmach, Janice Regina (2009)
The growing modernization in agricultural production and the use of small and high cost seeds, usually with the waste of sowing and the disposal seedlings recommend the use of techniques such as pelleting of seeds. However, the use of pelleted seeds may present some problems because the pellet formed around the seed can affect their performance during the germination. The cultivation of tobacco is in itself one of the major agricultural activities in the South Region of Brazil, due to the system of production that allows the cultivation in small areas, with profit to small farmers, giving it relevant socioeconomic role, besides providing raw material for a major industrial complex. Its planting is done through seeds, whose small size hinders its handling, these seeds have difficulties in germination, showing dormancy varying levels in pelleted seeds, a fact that is not seen in raw seeds. This study aimed to verify the efficiency of the use of GA3 and KNO3 as a method of overcoming dormancy in tobacco pelleted seeds, as well as use of two methods for evaluation of tobacco pelleted seeds germination. The results show that the potassium nitrate showed higher percentage of germination in pelleted seeds in both varieties and that the methodology UC (moisture continues) is more sensitive to responses of tobacco pelleted seeds.